Intra Strain Variation of the Effects of Gram-Negative ESKAPE Pathogens on Intestinal Colonization, Host Viability, and Host Response in the Model Organism Caenorhabditis elegans - Scott, Euan; Holden-Dye, Lindy; O’Connor, Vincent; Wand, Matthew E. (Frontiers in Microbiology, 2020)
In its native environment of rotting vegetation the soil nematode Caenorhabditis elegans hosts a range of bacteria. This includes species from the ESKAPE group of pathogens that pose a clinical problem in acquired hospital infections. Here, we investigated three of the Gram-negative members of the ESKAPE group, Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumannii. Pathogenicity profiles as measured by time to kill adult C. elegans showed that P. aeruginosa was the most pathogenic, followed by K. pneumoniae, whilst C. elegans cultured on A. baumannii exhibited the same survival as those on the standard laboratory food source for C. elegans, E. coli OP50. The pathogenicity was paralleled by a reduction in time that C. elegans resided on the bacterial with the most pathogenic strains triggering an increase in the frequency of food-leaving. Previous reports indicate that gut colonisation is a feature of pathogenicity, but we found that the most pathogenic strains were not associated with the highest colonisation. Indeed, clearance of P. aeruginosa strains from the C. elegans gut was independent of bacterial pathogenicity. We show that this clearance is regulated by neuromodulation as mutants unc-31 and egl-3 have enhanced clearance of P. aeruginosa. Intriguingly this is also not linked to their pathogenicity. It is likely that there is a dynamic balancing occurring in the C. elegans intestinal environment between maintaining a healthy, beneficial microbiota and removal of pathogenic bacteria.